The crime of genocide "The Yazidis as a case" - Ahmad Alrawy; Abdulaziz Alkhataby (الرافدین للحقوق, 2024)
The seismic impact of the Second World War on the landscape of international criminal law is notably manifested in the conceptual evolution of genocide, propelled by the atrocities committed during this global conflict. Responding to these grave offenses, the international community endeavored to crystallize a precise definition for genocide, a mission realized with the establishment of the Convention on the Prevention and Punishment of the Crime of Genocide in 1948. In tandem with legislative efforts, criminal jurisprudence undertook the task of refining the definition, delineating various forms of genocide, including physical, biological, and cultural manifestations. Key attributes associated with genocide emerged, notably its non-political nature, intentional commission, and exemption from the statute of limitations. The term "genocide" underwent further refinement with the ratification of the Statute of the International Criminal Court in 1998. The crime of genocide, as outlined in this statute, encompasses three core elements. The material element encapsulates criminal conduct, defined through five distinct forms: killing members of a targeted group, inflicting severe physical or mental harm, intentionally subjecting the group to conditions facilitating its outright or partial destruction, implementing measures to prevent childbirth within the group, and forcibly transferring children from the group. The moral element necessitates both a general intent for the crime and a specific intent for partial or complete destruction. Furthermore, the international element designates genocide as a crime falling under the jurisdiction of international law, governed by its own convention and the statutes of the International Criminal Court.